2018
DOI: 10.1016/j.cej.2017.11.064
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the mechanisms of how poly aluminium chloride inhibits short-chain fatty acids production from anaerobic fermentation of waste activated sludge

Abstract: It is generally believed that the preference ranking method PROMETHEE has a quadratic time complexity. In this paper, however, we present an exact algorithm that computes PROMETHEE's net flow scores in time O(qn log(n)), where q represents the number of criteria and n the number of alternatives. The method is based on first sorting the alternatives after which the unicriterion flow scores of all alternatives can be computed in one scan over the sorted list of alternatives while maintaining a sliding window. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(31 citation statements)
references
References 50 publications
3
25
1
Order By: Relevance
“…This provided sludge cells better protection and slowed down the solubilization process. Furthermore, Chen et al (2018) verified that with the increase of PACl addition from 0 to 40 mg Al/g of total suspended solids, SCFA yield decreased from 212.2 to 138.4 mg COD/g volatile suspended solids. Kooijman, Kreuk, and Lier (2017) investigated the dewaterability of CEPT sludge and the results indicated that CEPT sludge has a shorter capillary suction time (CST) value compared to sludge without chemical addition, which is probably due to the lower fraction of small particles in the CEPT sludge (Kooijman et al, 2017).…”
Section: Research Articlesupporting
confidence: 52%
See 2 more Smart Citations
“…This provided sludge cells better protection and slowed down the solubilization process. Furthermore, Chen et al (2018) verified that with the increase of PACl addition from 0 to 40 mg Al/g of total suspended solids, SCFA yield decreased from 212.2 to 138.4 mg COD/g volatile suspended solids. Kooijman, Kreuk, and Lier (2017) investigated the dewaterability of CEPT sludge and the results indicated that CEPT sludge has a shorter capillary suction time (CST) value compared to sludge without chemical addition, which is probably due to the lower fraction of small particles in the CEPT sludge (Kooijman et al, 2017).…”
Section: Research Articlesupporting
confidence: 52%
“…This provided sludge cells better protection and slowed down the solubilization process. Furthermore, Chen et al () verified that with the increase of PACl addition from 0 to 40 mg Al/g of total suspended solids, SCFA yield decreased from 212.2 to 138.4 mg COD/g volatile suspended solids.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although this process is very useful in protecting natural water bodies from pollution, large amounts of waste activated sludge (WAS) are inevitably produced as the major byproduct. WAS contains high levels of pathogens, heavy metals and other toxic and hazardous substances (Chen et al, 2018; Wang et al, 2018), and therefore requires to be effectively treated before its final disposal. On the other hand, WAS contains a lot of organics such as protein and carbohydrates, which make it a valuable resource (Wang et al, 2017a(Wang et al, , 2017b.…”
Section: Introductionmentioning
confidence: 99%
“…Protein was measured using the Lowry's method with BSA as the standard (Lowry et al, 1951). SCFA was performed by gas chromatography, and the operation procedures were according to our previous study and detailed in Supplementary data (Chen et al, 2018). The activity of key hydrolytic enzymes (protease) and acetate-forming enzymes (acetate kinase (AK)) were measured according to previous study (Goel et al, 1971;Feng et al, 2009).…”
Section: Methodsmentioning
confidence: 99%